Implementation of a Competency-Based, Interdisciplinary Pediatric Palliative Care Curriculum Using Content and Format Preferred by Pediatric Residents - Meaghann S. Weaver; Christopher Wichman (MDPI AG, 2018)
Palliative care competencies at the pediatric resident training level expand learned knowledge into behavior. The objective of this study was to investigate mode of palliative care education delivery preferred by pediatric residents and to report on participatory approach to resident palliative care curriculum design. A one-hour monthly palliative care curriculum was designed and implemented in a participatory manner with 20 pediatric residents at a free-standing Midwestern children’s hospital. Outcome measures included pediatric residents’ personal attitude and perceived training environment receptivity before and after implementation of a palliative care competency-based curriculum. An 18-item survey utilizing Social Cognitive Theory Constructs was administered at baseline and after palliative care curriculum implementation (2017⁻2018 curricular year). Pediatric residents prioritized real case discussions in group format (16/20) over other learning formats. Topics of highest interest at baseline were: discussing prognosis and delivering bad news (weighted average 12.9), pain control (12.3), goals of care to include code status (11.1), and integrative therapies (10.7). Summary of ordinal responses revealed improvement in self-assessment of personal attitude toward palliative care and training environment receptivity to palliative care domains after year-long curriculum implementation. Curricular approach which is attentive to pediatric residents’ preferred learning format and self-assessment of their behaviors within their care setting environment may be beneficial in competency-based primary palliative training.